2016
DOI: 10.3746/pnf.2016.21.4.348
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Black Garlic after Different Thermal Processing Steps

Abstract: This study investigated the physicochemical characteristics of black garlic (BG) after different thermal processing steps. Compared with fresh garlic (FG), the moisture content and pH in BG decreased significantly, while the ash content and browning intensity increased during thermal processing. The total mineral and the free sugar contents were significantly higher than that of the BG2 and BG4 samples, respectively. The free sugar content increased by 16-fold in the BG cloves compared with that of FG, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 22 publications
5
67
1
2
Order By: Relevance
“…In general, the rate of moisture removal increases with temperature and the pH also decreases more significantly in garlic heated at high temperatures (Bae et al, 2014). Besides moisture changes, a continuous decrease in pH from initial levels of around 6.3-6.2 to values of 4.0-3.7, depending on the processing conditions, was produced (Kang, 2016;Zhang et al, 2016), with this decrease being accompanied by an increase in total acids content (5 g/kg in FG and 31-38 g/kg in BG); this fact may be related to the bittersweet taste in BG. Sun and Wang (2018) studied the evolution of acids present in BG elaborated at 65, 75 and 85 °C and observed that the highest acid concentration (6%) was obtained at 75 °C after 12 days.…”
Section: Sensory Propertiesmentioning
confidence: 97%
“…In general, the rate of moisture removal increases with temperature and the pH also decreases more significantly in garlic heated at high temperatures (Bae et al, 2014). Besides moisture changes, a continuous decrease in pH from initial levels of around 6.3-6.2 to values of 4.0-3.7, depending on the processing conditions, was produced (Kang, 2016;Zhang et al, 2016), with this decrease being accompanied by an increase in total acids content (5 g/kg in FG and 31-38 g/kg in BG); this fact may be related to the bittersweet taste in BG. Sun and Wang (2018) studied the evolution of acids present in BG elaborated at 65, 75 and 85 °C and observed that the highest acid concentration (6%) was obtained at 75 °C after 12 days.…”
Section: Sensory Propertiesmentioning
confidence: 97%
“…Garlic contains a variety of minerals (0.72% to 0.84% of FM) that are beneficial to humans including their contributions to antihypertension and anticancer activity, immune development, and suppression of oxidation and respiratory tract infections (Houston & Harper, ; Rayman, ; USDA, ). Potassium was found to be the most abundant mineral (60.49 mg/g DM), followed by sulfur (11.38 mg/g DM), magnesium (2.76 mg/g DM), sodium (2.46 mg/g DM), and calcium (1.04 mg/g DM) in FG (Kang, ). Using inductively coupled plasma atomic emission spectroscopy, Kang () found significant changes in the mineral profile of garlic upon different thermal treatments: Processing of garlic at 65 °C and 50% relative humidity for 192 hr led to elevated levels of zinc, potassium, magnesium, iron, manganese, phosphorous, selenium, copper, sodium, calcium, and sulfur, with the increase of selenium being the greatest (160%), followed by sodium (61.41%), iron (41.88%), and calcium (24.92%).…”
Section: Characteristic Components and Their Formation Mechanisms In Bgmentioning
confidence: 99%
“…The first and second extracts were combined, and the absorbance of the hexane solution was measured at 254 nm (Kang, 2016). The thiosulfinate content of the hexane solution was calculated using the following equation:…”
Section: Thiosulfinate Contentmentioning
confidence: 99%